A STUDY TO EVALUATE THE EFFECTS OF MULTIPLE ORAL DOSES OF BILASTINE, DESLORATADINE, AND LEVOCETIRIZINE ON PSYCHOMOTOR PERFORMANCE AND SALIVARY FLOW IN PATIENTS WITH CHRONIC URTICARIA ATTENDING DERMATOLOGY OUTPATIENT DEPARTMENT AT A TERTIARY CARE CENTER - IMRAN KHAN; PADMAJA MEKALA; ASIYA BEGUM; USHARANI PINGALI; SUMEDH GK (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Antihistamines are the most used systemically delivered medications for skin conditions that can inhibit cholinergic (muscarinic) receptors and block central H1 receptors leading to effects such as dryness of mouth and sedation, respectively. Bilastine, desloratadine, and levocetirizine are second-generation antihistamines which have variable effects on dryness of mouth and sedation; hence, the objective of this study is to evaluate any differences in these effects in chronic urticaria patients prescribed the above-mentioned antihistamine drugs. Methods: Subjects with chronic urticaria who were prescribed any of the three antihistamines by the dermatologist were enrolled. Baseline readings of salivary flow by cotton ball method and psychometric performances by digit letter substitution test (DLST), six letter cancellation test (SLCT), card sorting test, and Visual Analog Scale (VAS) for dryness of mouth and sedation measured before administration of prescribed antihistaminic drug and compared with readings taken of the same tests after 7 days of antihistaminic drug administration. Results: A total of 36 subjects were enrolled median age of 38.5 years (range 18–57 years) and 55% (20/36) were males. Reduction in the mean salivary flow and the psychomotor performance were not significantly different between the three drug groups, although there were reductions in the three groups in the outcome measures salivary flow and psychomotor performance tests including DLST and SLCT when compared to baseline. Conclusion: The three drugs are similar with respect to their adverse effect profile in terms of causing dryness of mouth and impairment of psychomotor performance.